The Engine 2 cookbook : more than 130 lip-smacking, rib-sticking, body-slimming recipes to live plant-strong - Esselstyn, Rip; Esselstyn, Jane (Grand Central Life & Style, 2017)
With this highly anticipated follow-up to the runaway bestseller "The Engine 2 Diet" readers can bring the Engine 2 program into their kitchens with these 130 plus delicious recipes from former firefighter turned vegan advocate Rip Esselstyn and his sister Jane Esselstyn. Print run 60,000.